THE EFFECT OF A PROJECT-BASED LEARNING MODEL ON EXPOSITORY TEXT WRITING SKILLS - Sakaria Sakaria; Usman Usman; Vivi Febriyanti (Universitas Negeri Makassar, 2024)
This study aims to examine the effect of project-based learning model on the ability to write exposition text in class VIII SMPN 20 Bulukumba. This research is a type of quantitative research with pre-experimental design. The research design used in this study was one group pretest-posttest. The population in this study were 179 students of class VIII A SMP 20 Bulukumba. The sample in this study was 30 students. The data collection technique in this study was a test technique in the form of a writing task. The collected data were analysed with descriptive statistics and inferential statistics. The results showed that the project-based learning model had an effect on students' learning to write exposition texts. The project-based learning model can help students solve problems as well as provide opportunities for students to describe their creativity and help teachers to increase student learning motivation, think critically, and develop social skills, and achieve maximum exposition text writing ability.